(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study involved men aged 60–65 years. The course of intermittent normobaric hypoxia (APG) was carried out for 3 weeks. Before and after the course of hypoxia, respiratory volume, frequency and minute volume of respiration, oxygen consumption, carbon dioxide release, blood pressure, minute volume of blood circulation, heart rate, erythrocyte count, hemoglobin, saturation, content and rate of oxygen transport by arterial blood, oxygen capacity of blood were determined. Before and after the APG course, the level of general physical performance was determined using a bicycle ergometric test (PWC150) in a modification for the elderly. It has been established that the course of APG leads to an increase in the body’s resistance to hypoxia, economization of the functions of the cardiorespiratory system, with an increase in the number of red blood cells, hemoglobin, oxygen capacity of blood and the efficiency of oxygen utilization by tissues, which contributes to an increase in the overall physical performance of elderly people.